2018
DOI: 10.1080/21691401.2018.1505738
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Biotinylated naringenin intensified anticancer effect of gefitinib in urethane-induced lung cancer in rats: favourable modulation of apoptotic regulators and serum metabolomics

Abstract: Co-therapy through biotin modified nanoparticles (NPs) of gefitinib (Gnb) and naringenin (Nar) was investigated for its therapeutic and synergistic potential against lung cancer. The biotin-conjugated polymeric NPs (bty-Nar/Gnb) were developed using oil in water emulsion technique and optimized using central composite design. The formulations were subjected to various in vitro (A549 cell lines) and in vivo evaluations in urethane-induced lung cancer. Co-administration of Gnb and Nar NPs displayed a significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 46 publications
(54 reference statements)
2
7
0
Order By: Relevance
“…Similarly, the Naringenin‐SLNs prepared by Ji et al, was not toxic to A549 cell at a concentration range of 1–50 µg/ml for 72 hr (Ji et al., 2016). In contrast, Parashar et al, reported that biotinylated Naringenin significantly decreased the proliferation of A549 cell with a IC 50 value of 37.46 ± 0.86 µM (Parashar et al., 2018). Our Naringenin‐loaded LCNs formulation was more potent than Naringenin‐SLNs, biotinylated Naringenin, and powder Naringenin in terms of inhibiting the proliferation of the A549 cells.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, the Naringenin‐SLNs prepared by Ji et al, was not toxic to A549 cell at a concentration range of 1–50 µg/ml for 72 hr (Ji et al., 2016). In contrast, Parashar et al, reported that biotinylated Naringenin significantly decreased the proliferation of A549 cell with a IC 50 value of 37.46 ± 0.86 µM (Parashar et al., 2018). Our Naringenin‐loaded LCNs formulation was more potent than Naringenin‐SLNs, biotinylated Naringenin, and powder Naringenin in terms of inhibiting the proliferation of the A549 cells.…”
Section: Discussionmentioning
confidence: 94%
“…prostate, pancreatic, colon, breast, and gastric cancer (Song et al, 2016;Lim et al, 2017;Wang et al, 2019a) sensitizing chemotherapy CDKN2A, BCL2, CASP3/9, BAX, PTK2, MAPK14 lung and pancreatic cancer (Parashar et al, 2018;Lee et al, 2019) inhibiting metabolism AKT1, GTF2H2, MAP2K1/2, MAPK1, NFKB1, PIK3CA breast cancer (Harmon and Patel, 2004) enhancing immunity GZMB, ID2, IFNG, IRF2, SMAD3/7 lung cancer and melanoma (Lian et al, 2018) Naringin anti-proliferation AKT1, BIRC5, CDKN1A, CTNNB1, EGFR, MAPK1, MIR126, MTOR, NFKB, PIK3CA, VCAM1…”
Section: Discussionmentioning
confidence: 99%
“…Co-administration of gefinitib and naringenin NPs promoted enhanced cell apoptosis while regulating the serum metabolites and biochemical parameters to normal levels. The cotherapy caused a remarkable increase in the pro-apoptotic proteins (BAX and caspase-9) and reduced anti-apoptotic proteins (MMP-9, P-16 and Bcl-2) (Parashar et al, 2018b). Parteek and coworkers also indicated that, entrapment of naringenin into hyaluronic acid-chitosan-PCL NPs, by utilizing layer by layer technique, is effective in targeting lung cancer cells.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%